Joanna Wiszniewska, Zakaz reklamy aptek iich działalności, seria Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2019, ss. 292, ISBN 978-83-8158-229-2 - Jankowska, Paulina (Studia Prawa Publicznego, 2019)
Joanna Wiszniewska, Zakaz reklamy aptek iich działalności, seria Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2019, ss. 292, ISBN 978-83-8158-229-2